Systemic Consequences of Anorexia Nervosa: Multiorgan Disfunction and Long-Term Complications - Mazurek, Katarzyna; Gęborys, Anna; Wojcieszak, Maja; Kania, Joanna; Miazga, Dominika; Maziarczyk, Alicja; Białogłowski, Michał; Kutnik, Kacper; Woźnica, Weronika; Dąbrowska, Julia (Quality in Sport, 2026)
Background. Anorexia nervosa is a serious eating disorder marked by constant restriction of food intake, fear of gaining weight and disturbances in body image perception. While it is primarily categorized as a psychiatric illness, prolonged undernutrition leads to extensive medical complications that involve multiple organ systems and substantially increase mortality. These systemic effects are frequently overlooked, despite their critical role in disease severity and clinical outcomes. Aim. The aim of this study was to present anorexia nervosa as a complex multisystem condition by outlining the key pathophysiological processes and medical complications affecting major organ systems, and emphasize the necessity of early diagnosis, coordinated multidisciplinary care, and long-term medical observation. Material and methods. This review synthesizes current evidence by examining literature from 2019-2025 available on PubMed and Google Scholar using the keywords „anorexia nervosa”, „malnutriton”, „medical complications”. Results. It has been found that anorexia nervosa causes widespread medical complications that involve many organ systems, including the skeletal, endocrine, reproductive, digestive, cardiovascular, haematopoietic and respiratory system. The most serious consequences include sudden cardiac death, severe osteoporosis, infertility, obstetric problems and dysregulation of multiple hormonal axes. Even after restoration of normal nutrition, some complications may not fully resolve. Conclusions. Anorexia nervosa is a life-threatening disorder with systemic consequences that extend beyond weight loss, affecting multiple organs and physiological systems. Therefore, rapid intervention, comprehensive care and constant medical surveillance are crucial to improve long-term treatment outcomes. Key words: anorexia nervosa, malnutrition, energy deficiency, medical complications, multidisciplinary care